PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE CIRC UNTUK MENINGKATKAN MOTIVASI DAN PRESTASI BELAJAR - Anton Budiono (DIADIK, 2024)
The purpose of this study is to, 1). Describes the application of the Cooperative Integrated Reading and Composition (CIRC) learning model in increasing students' learning motivation. 2). Describes the application of the Cooperative Integrated Reading and Composition (CIRC) learning model in improving student achievement. 3). Describes that CIRC learning activities can increase the motivation and learning achievement of 5th graders of SD Negeri 01 Air Manjunto, Sido Makmur Village, Air Manjunto District. In this study, the Class Action Research (CAR) method was used and continued with experimental research. The subjects of this study were 5th grade students of SD Negeri 01 Air Manjunto. Data collection techniques used in the study were observation sheets and student test methods. Analysis of the data used values are 1) Analysis of teacher assessment instruments, 2) Analysis of students' learning motivation instruments, 3) Analysis of pre-test and post-test scores, 3) T-test analysis of student achievement. The instrument of validation of students' motivation and achievement in the research used was the CIRC type of cooperative learning model. The conclusions of this study are: 1). The application of the CIRC type of cooperative learning model can increase students' learning motivation in Indonesian language subjects, 2). The application of the CIRC type cooperative learning model can improve student achievement in Indonesian subjects at SD Negeri 01 Air Manjunto in the first semester of the 2022/2023 academic year, and 3). The application of the CIRC type cooperative model in increasing students' motivation and learning achievement compared to conventional learning models